Pharmacokinetics and relative bioavailability of fixed-dose combination of clopidogrel and aspirin versus coadministration of individual formulations in healthy Korean men - Choi HK; Ghim JL; Shon J; Choi YK; Jung JA (Dove Medical Press, 2016)
Hyang-Ki Choi,1 Jong-Lyul Ghim,2 Jihong Shon,1,3 Young-Kyung Choi,1 Jin Ah Jung1,3 1Department of Pharmacology, Inje University College of Medicine, Busan, Republic of Korea; 2Department of Clinical Pharmacology and Toxicology, Anam Hospital, Korea University College of Medicine, Seoul, Republic of Korea; 3Department of Clinical Pharmacology, Inje University Busan Paik Hospital, Busan, Republic of Korea Background: Simultaneous prescription of clopidogrel and low-dose aspirin is recommended for the treatment of acute coronary syndrome because of improvements in efficacy and patient compliance. In this study, the pharmacokinetics of a fixed-dose combination (FDC) of clopidogrel and aspirin was compared with coadministration of individual formulations to clarify the equivalence of the FDC. Methods: This was a randomized, open-label, two-period, two-treatment, crossover study in healthy Korean men aged 20–55 years. Subjects received two FDC capsules of clopidogrel/aspirin 75/100 mg (test) or two tablets of clopidogrel 75 mg and two capsules of aspirin 100 mg (reference) with a 14-day washout period. Plasma concentrations of clopidogrel, aspirin, and salicylic acid were measured using validated ultraperformance liquid chromatography–tandem mass spectrometry. Bioequivalence was assessed by analysis of variance and calculation of the 90% confidence intervals (CIs) of the ratios of the geometric means (GMRs) for AUClast and Cmax for clopidogrel and aspirin. Results: Sixty healthy subjects were enrolled, and 53 completed the study. Clopidogrel, aspirin, and salicylic acid showed similar absorption profiles and no significant differences in Cmax, AUClast, and Tmax between FDC administration and coadministration of individual formulations. The GMRs (90% CI) for the Cmax and AUClast of clopidogrel were 1.08 (0.95, 1.23) and 0.93 (0.84, 1.03), respectively. The GMRs (90% CI) for the Cmax and AUClast of aspirin were 0.98 (0.84, 1.13) and 0.98 (0.93, 1.04), respectively. Both treatments were well tolerated in the study subjects. Conclusion: The FDC of clopidogrel and aspirin was bioequivalent to coadministration of each individual formulation. The FDC capsule exhibited similar safety and tolerability profiles to the individual formulations. Therefore, clopidogrel/aspirin 75 mg/100 mg FDC capsules can be prescribed to improve patient compliance. Keywords: comparative pharmacokinetics, fixed-dose combination, clopidogrel/aspirin, bioequivalence